Next Generation Sweet Potato Production in the Caribbean - Ainsworth, Riley (2025)
In collaboration with National Agricultural Research Systems (NARS), FAO’s International Treaty on Plant Genetic Resources for Food and Agriculture and the Inter-American Institute for Cooperation on Agriculture (IICA)